Negotiating intersubjectivity by interpersonal and appraisal shifts in Chinese-English government press conference interpreting - Xu, Jun; Liang, Yuxiao (Frontiers in Psychology, 2023)
This article investigates how interpreting shifts of interpersonal and appraisal resources facilitate the successful negotiation of intersubjectivity at China’s premier press conferences (PPCs) from 2016 to 2021. This article conducts a corpus-based critical discourse analysis of interpersonal shifts at the PPCs as defined by systematic functional linguistics. Quantitative results show that the interpreter is strongly inclined to utilize appraisal shifts which enhance (or soften) the positive (or negative) evaluations of the Chinese government in interpreting the journalists’ questions and use shifts to first-person plurals and inclinational modal verbs in interpreting the Chinese Premier’s answers. Qualitative results show these shifts facilitate the direct or indirect reproduction of the government’s official ideology (especially the notions of solidarity, change, resolution, and people’s well-being) and the existing power relations between the government, media, and the Chinese people (both authority and solidarity). It is concluded that the interpreter displays a strong tendency to use interpersonal shifts to ensure successful negotiation of intersubjectivity at the PPCs by ultimately reproducing the social status quo.